Oncologic results of the surgical salvage of recurrent laryngeal squamous cell carcinoma in a multicentric retrospective series: Emerging role of supracricoid partial laryngectomy. Issue 1 (17th April 2014) - de Vincentiis, Marco; De Virgilio, Armando; Bussu, Francesco; Gallus, Roberto; Gallo, Andrea; Bastanza, Giovanni; Parrilla, Claudio; Greco, Antonio; Galli, Jacopo; Turchetta, Rosaria; Almadori, Giovanni; Pagliuca, Giulio; et al.
Abstract Background Several studies in the last decade evaluated conservative surgical procedures and, in particular, supracricoid operations as an alternative to total laryngectomy for the salvage of recurrences of laryngeal squamous cell carcinoma (SCC) after a first attempt of organ preservation. Methods The clinical records of 68 consecutive patients primarily treated by irradiation or endoscopic surgery and surgically salvaged by total laryngectomy or supracricoid partial laryngectomy in 2 large university hospitals in Italy from 2004 to 2010 were reviewed. Results The survival was not affected by the primary treatment or by salvage modality. The only parameter always keeping a prognostic value is the involvement of resection margins of salvage surgery. Patients with early relapse seem to have a worse prognosis than patients with a delayed relapse (p = .05 at Cox multivariate analysis and p = .048 at Wilcoxon test for overall survival [OS] from the primary treatment). Conclusion Supracricoid operations, if the indications are careful, can prove reliable salvage procedures. © 2014 Wiley Periodicals, Inc. Head Neck37: 84–91, 2015